ANALISIS KINERJA PENYULUH PERTANIAN DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Supiyani Wati; Rosnita '; Cepriadi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to analyzedthe execution of counseling and analyzedthe performance of agricultural extension officer, in the district of Gunung Toar Regency Kuantan Singingi.Research using survey method was carriate out from November fill April 2015 in sub Gunung Toar district Kuantan Singingiwith the largest amounted of rubber farmers and a rubber plant large a mount in Riau Province. Sampling is caried out againts census 5 extension officers in the UPTD plantation sub Gunung Toar. Execution of counseling in analistis are descriptive and extension officers motivation with scale likert. The motivational variable refers to the theory of extension officers in Kadarisman Saydam (2012), with respect to internal and external factors. Research results show that the extention of counseling in the sub Gunung Toar was alreadygood, where the extension officers LAKU system using the methods with the extension in the form of print, extension officers amountedto 5 people with education level of 60 percent SMA/SMK/equal and 40 percent of the graduates, number of villages built average 2-4 village per extension officers. The perfoemance extension officers in the district of Gunung Toar Regency Kuantan Singingi was “Good enough” score average (3,79).   Keyword:Agricultural extension officer, execution of counseling, performance extention officers